OMNIBUS LAW SEBAGAI STRATEGI PENATAAN REGULASI PERTANAHAN - Lainsamputty, Natanel; Soplantila, Ronny; Hetharie, Yosia (Faculty of Law, Universitas Pattimura, 2020)
The Indonesian government has gone through government regimes ranging from the Old Order to the Reformation Order to date which also has an impact on statutory provisions including land policies which are constantly changing and causing overlapping of various regulations as one of the triggers for land conflicts. In order to overcome the overlapping issue of land regulations, a new breakthrough was born through the concept of the Omnibus Law from the government as a strategy and solution for structuring land regulations. Through the Omnibus Law concept, it is hoped that it can resolve land conflicts due to overlapping regulations quickly, precisely and efficiently, and can organize and harmonize various land regulations from the central to regional levels. With the effective and efficient arrangement of land regulations, it will support the improvement of the investment climate in Indonesia.